Organotypic co-cultures as a novel 3D model for head and neck squamous cell carcinoma - Engelmann, Luca; Thierauf, Julia; Laureano, Natalia K.; Stark, Hans-Jürgen; Prigge, Elena-Sophie; Horn, Dominik; Freier, Kolja; Grabe, Niels; Rong, Chao; Federspil, Philippe A.; Plath, Karim; Plinkert, Peter K.; et al. (Cancers, 2020)
Background: Head and neck squamous cell carcinomas (HNSCC) are phenotypically and molecularly heterogeneous and frequently develop therapy resistance. Reliable patient-derived 3D tumor models are urgently needed to further study the complex pathogenesis of these tumors and to overcome treatment failure. Methods: We developed a three-dimensional organotypic co-culture (3D-OTC) model for HNSCC that maintains the architecture and cell composition of the individual tumor. A dermal equivalent (DE), composed of healthy human-derived fibroblasts and viscose fibers, served as a scaffold for the patient sample. DEs were co-cultivated with 13 vital HNSCC explants (non-human papillomavirus (HPV) driven, n = 7; HPV-driven, n = 6). Fractionated irradiation was applied to 5 samples (non-HPV-driven, n = 2; HPV-driven n = 3). To evaluate expression of ki-67, cleaved caspase-3, pan-cytokeratin, p16INK4a, CD45, ∝smooth muscle actin and vimentin over time, immunohistochemistry and immunofluorescence staining were performed Patient checkup data were collected for up to 32 months after first diagnosis. Results: All non-HPV-driven 3D-OTCs encompassed proliferative cancer cells during cultivation for up to 21 days. Proliferation indices of primaries and 3D-OTCs were comparable and consistent over time. Overall, tumor explants displayed heterogeneous growth patterns (i.e., invasive, expansive, silent). Cancer-associated fibroblasts and leukocytes could be detected for up to 21 days. HPV DNA was detectable in both primary and 3D-OTCs (day 14) of HPV-driven tumors. However, p16INK4a expression levels were varying. Morphological alterations and radioresistant tumor cells were detected in 3D-OTC after fractionated irradiation in HPV-driven and non-driven samples. Conclusions: Our 3D-OTC model for HNSCC supports cancer cell survival and proliferation in their original microenvironment. The model enables investigation of invasive cancer growth and might, in the future, serve as a platform to perform sensitivity testing upon treatment to predict therapy response.
Gesehen am 14.12.2020